Measuring Income Tax Discrimination - Kakwani, Nanak C.; Lambert, Peter J. (The Review of Economics and Statistics, 1999)
We propose a procedure for measuring the effect of systematic discrimination in the income tax. Different socioeconomic groups are assumed to face different tax schedules. We show that a welfare loss is caused by the group specificity of schedules, the dollar value of which is our measure of discrimination. Defining vertical equity as the dollar value of the tax system's welfare superiority over an equal yield flat tax, discrimination equates to a loss in vertical equity. The Australian income tax is found to discriminate against wage and salary earners, causing a roughly 1% loss of social welfare in 1984.